Keragaman Genetik Inbrida Jagung QPM dan Provit-A Berdasarkan Marka SSRs (Simple Sequence Repeats) - Andayani, Nining Nurini; H.G, M. Yasin; Pabendon, Marcia B. (Jurnal Penelitian Pertanian Tanaman Pangan, 2016)
Information on genetic diversity of QPM and Provit-A maize germplasm is important to support breeding program, in order to form a high yielding maize hybrid. Simple sequence repeats (SSR) have been extensively utilized as genetic markers to study the genetic diversity, cultivar identification, and gene mapping. The objectives of this research were to investigate the genetic diversity and to obtain information the genetic relationship among 20 maize accessions using 29 SSRs. The research was carried out at the Moleculer Biology Laboratory of Indonesian Cereals Research Institute (ICERI) in Maros, South Sulawesi. Twenty nine polymorphic primers that covered the 10 maize chromosomes were used to fingerprint the genotype of the lines, detecting 83 allels, with an average allel number of 3 allels per locus, ranging from 2 to 6 alleles per locus. The results indicated that polymorphism information content (PIC) ranged from 0.10 (nc133 and phi072) to 0.74 (phi064) with the average of 0.45. Genetic distance based on genetic similarity estimate ranged from 0.39 to 0.92. The high level of PIC values and wide genetic distances indicated the large variability among maize germplasm. Cluster analysis divided the 20 maize accessions into three groups. Coefficient cofenetic value (r) was 0.85 indicated a good fit based on the genetic similarity value. As many as 30 inbred heterotic recombinants were derived by incorporating 20 QPM and Provit-A with genetic distance of â‰¤0.65. The SSRs proved to be reliable and is practical technique for revealing the relationship among specialty maize genotypes.